A robust 3D host for sodium metal anodes with excellent machinability and cycling stability. Issue 68 (4th July 2018) - Xiong, Wan-Sheng; Jiang, Yun; Xia, Yu; Qi, Yuyang; Sun, Weiwei; He, Dan; Liu, Yumin; Zhao, Xing-Zhong
Abstract : A robust and ultra-stable sodium infiltrated Fe2 O3 coated carbon textile (SFCT) anode has been designed. This SFCT anode overcomes the disadvantage of Na electrodes, which is not easily processable, and exhibits more flat voltage profiles, lower stripping/plating overpotential, and better cycling stability in an additive-free carbonate-based electrolyte compared with bare Na electrodes. Abstract : This study demonstrates a robust and ultra-stable sodium infiltrated Fe2 O3 coated carbon textile (SFCT) anode with excellent machinability. The obtained SFCT anode overcomes the disadvantage of Na electrodes, which is not easily processable, and exhibits more flat voltage profiles, lower stripping/plating overpotential, and better cycling stability in an additive-free carbonate-based electrolyte compared with bare Na electrodes.